CFD investigation on the potential of solar induced ventilation in enhancing the stack ventilation performance for hot and humid climate - Sapian, Abdul Razak (s.n, 2012)
The climatic conditions in Malaysia have resulted in small air temperature differences between the indoor and outdoor of naturally ventilated buildings. This has reduced the efficiency of stack ventilation. A viable alternative in enhancing stack ventilation is the utilization of solar induced ventilation. In the present research, solar induced ventilation that utilizes roof solar collector and vertical stack is proposed. The proposed solar induced ventilation is developed for application in small and medium enterprise (SME) premise. The aim is to enhance the air flow rate at the indoor working area. Three research tools have been utilized, namely physical experiment, analytical method and simulation modelling. A prototype of the proposed solar induced ventilation is constructed in the physical experiment. The purpose of physical experiment is to examine the prototype’s ability to induce stack ventilation in hot and humid climate. The physical experimental results are compared with analytical method results in verifying the external factors that affect the induced ventilation of the prototype. The potential performance of the prototype is further determined using simulation modelling. The investigations involve the effective orientation for the prototype’s solar collector and the effect of vertical stack height on the air temperature and mass flow rate inside the stack. This method is also employed in investigating the prototype application at the selected typology of SME building, which is a single storey shophouse. Results are analyzed and presented in term of four variables, namely temperature, air velocity, mass flow rate and air flow rate. The findings from physical experiment show that the prototype is able to induce stack ventilation in hot and humid climate. High air temperature difference between the stack air and the ambient air is attained by the prototype, which is 9.9 ºC, for 877 W/m² solar radiation incidents. The simulation modelling of prototype’s solar collector orientation shows that the recommended orientation throughout the year is west-facing. Meanwhile, the simulation modelling of vertical stack height indicates that the higher the stack is, the lower the air temperature inside the stack, but the greater the induced mass flow rate. The prototypes application in the selected single storey shophouse also demonstrates positive results, in which it is able to enhance the indoor air flow rate, as well as reduce the indoor air temperature. The prototype which has 1 meter width solar collector x 4 meter high vertical stack is able to reduce in average 0.6 ºC air temperature and increase air flow rate of less than 0.1 m³/s. The air temperature reduction and air flow rate increment are greater with the enhancement of prototype’s solar collector width. The recommended prototype’s solar collector width for the application at the selected single storey shophouse is 3 meter. In summary, the research shows potential application of solar induced ventilation that utilizes roof solar collector and vertical stack in enhancing stack ventilation in hot and humid climate. The research also contributes to the enhancement of stack ventilation in single storey industrial buildings in Malaysia.